Trends in domestic violence and firearm domestic violence during COVID-19 in five US cities - Tomsich, Elizabeth (Journal of family violence, 2025)
Purpose: The COVID-19 pandemic and resulting social and economic disruptions may be associated with increased risk for reported domestic violence (DV) and firearm-involved DV (FDV). This study examines trends in DV, FDV, and the proportion of DV incidents that involved firearms (FDV/DV) in five large US cities before and during the coronavirus pandemic. Method: We examined monthly trends in DV and FDV during January 1, 2018 through December 31, 2020, which included the early part of the pandemic, using Poisson or negative binomial regressions. We used binomial regressions to assess trends in FDV/DV. We considered the onset of the pandemic to be March 2020. Results: Findings varied across outcomes and cities. DV decreased in three cities: Kansas City (Incidence Rate Ratio (IRR), 0.88; 95% confidence interval (CI), 0.86-0.90), Los Angeles (IRR, 0.99; 95% CI, 0.99-1.00), and Nashville (IRR, 0.99; 95% CI, 0.99-1.00) relative to trends pre-pandemic. FDV increased in three cities: Chicago (IRR, 1.05; 95% CI, 1.02-1.08), Los Angeles (IRR, 1.08; 95% CI, 1.06-1.10), and Nashville (IRR, 1.03; 95% CI, 1.01-1.05) and decreased in one: Kansas City (IRR, 0.89; 95% CI, 0.87-0.90). FDV/DV increased in three cities: Chicago (Risk Ratio (RR), 1.04; 95% CI, 1.02-1.06), Los Angeles (RR, 1.09; 95% CI, 1.07-1.11), and Nashville (RR, 1.04; 95% CI, 1.02-1.06). Conclusions: We found variation among cities in trends in reported DV, FDV, and FDV/DV during the first months of the coronavirus pandemic. Variation may be due to a number of factors, including differences in baseline DV and FDV rates; economic strain and unemployment; compliance with social distancing; firearm ownership and purchasing; the availability of DV services; delays in court processing and the early release of prisoners; and community-law enforcement relations.